2018
DOI: 10.1161/jaha.118.009427
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cardiovascular Magnetic Resonance‐Derived Left Atrial Dimensions, Electroanatomical Substrate and NT‐proANP Levels in Atrial Fibrillation

Abstract: Background Enlargement of left atrial ( LA ) size indicates advanced disease stage in patients with atrial fibrillation ( AF ) and is associated with poor success of different AF therapies. Two dimensional echocardiographic LA measurements do not reliably reflect the true size of LA anatomy. The aim of the current study was: 1) to analyze cardiovascular magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…ANP has numerous biological effects, including blood pressure lowering effects and renin-angiotensin-aldosterone system (RAAS) inhibition [16,17,18,19,20]. It may affect apical Na channel and Na/K ATPasis basal activity, determining a decreased sodium reabsorption and increased Na excretion, leading to increased natriuresis [20].…”
Section: Natriuretic Peptides: From Molecular Evidences To Clinicamentioning
confidence: 99%
See 3 more Smart Citations
“…ANP has numerous biological effects, including blood pressure lowering effects and renin-angiotensin-aldosterone system (RAAS) inhibition [16,17,18,19,20]. It may affect apical Na channel and Na/K ATPasis basal activity, determining a decreased sodium reabsorption and increased Na excretion, leading to increased natriuresis [20].…”
Section: Natriuretic Peptides: From Molecular Evidences To Clinicamentioning
confidence: 99%
“…Recent studies focusing on AF patients found that NT-proANP levels correlate with AF type and LA dimensions [18]. Seewoster et al revealed that NT-proANP correlated with LA dimension as determined by cardiac magnetic resonance [18].…”
Section: Natriuretic Peptides: From Molecular Evidences To Clinicamentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we demonstrated that CMR-derived LA-EF is associated with AF progression phenotypes and the presence of LVAs. Although there was a significant association between NT-proANP and different LA size parameters, such as LA volume, anterior-posterior, superior-inferior and transversal diameter, the LA volume remained most significantly associated with biomarkers [1]. In another study, however, the association between advanced AF progression and LA-EF was stronger than with LA size only [2] .…”
mentioning
confidence: 77%